Trapping of giant-planet cores: I. Vortex aided trapping at the outer dead zone edge - Regály, Zsolt; Sándor, Zs; Csomós, P.; Ataiee, Sareh (Monthly notices of the Royal Astronomical Society, 2013)
Abstract. In this paper the migration of a 10 M⊕ planetary core is investigated at the outer boundary of the ‘dead zone’ of a protoplanetary disc by means of 2D
Gesehen am 20.12.2021